A novel inhibitor of C. elegans glutamate-activated chloride channel with potential anthelmintic activity - Turani, Ornella (2019)
Nematode parasitoses cause mortality and morbidity in humans and considerable losses in livestock, domestic animals and food crops. The acquisition of resistance to current anthelmintic drugs has prompted the search for new compounds. The free-living nematode Caenorhabditis elegans has emerged as a valuable platform for anthelmintic drug discovery. We have previously synthetized a small library of oxygenated tricyclic compounds and tested anthelmintic actions by measuring rapid effects on C. elegans. Exposure to dibenzo[b,e]oxepin-11(6H)-one (C1a) induced paralysis of C. elegans. We here sought to identify its target site and mechanism of action. Given that Cys-loop receptors are involved in worm locomotion and are targets of classical antiparasitic drugs, we tested the effects of C1a on several C. elegans mutant strains lacking these receptors. We found that a mutant strain that lacks the invertebrate glutamate-gated chloride-selective channel (GluClR), which is the target of the widely used antiparasitic ivermectin, is resistant to C1a. Thus, the paralysis assays revealed that GluClR is the main drug target of C1a. To unravel the molecular mechanism underlying the paralyzing action, we expressed in mammalian cells GluClα and β subunits to form GluClRs and evaluated the effects of C1a by electrophysiological whole-cell recordings. Glutamate elicited macroscopic currents from cells expressing GluClα/β heteromeric receptors whereas C1a was not capable of eliciting responses, thus indicating that it is not an agonist of GluClRs and that its mechanism differs from that of ivermectin. We found that C1a acts as an inhibitor of glutamate-responses: Preincubation of the cell with C1a produced a statistically significant decrease of the decay time constant and total charge and a slight decrease of the peak of currents elicited by glutamate. We here propose C1a as a novel compound or scaffold with promising antiparasitic activity mediated through inhibition of GluClRs.